Pengaruh Kompetensi, Komitmen Organisasi Pemerintah Desa dan Partisipasi Penganggaranterhadap Akuntabilitas dalam Pengelolaan Dana Desa (Studi Empiris pada Pemerintah Desa di Kabupaten Buleleng Barat) - Kasmini, Komang Lia Santi; Dewi, Nyoman Ayu Wulan Trisna (Universitas Pendidikan Ganesha, 2021)
AThe purpose of this study was to determine the effect of competence, organizational commitment of the village government and budgetary participation on accountability in the management of village funds. The method used in this study uses quantitative methods. Data was obtained through a data collection instrument in the form of a questionnaire measured by a Likert scale. The population used is the village government in West Buleleng Regency which consists of Banjar District, Serinit District, Busungbiu District and Gerokgak District. To determine the sample using the purposive sampling method with the criteria of respondents being the village head, village secretary and head of village financial affairs and obtained as many as 198 respondents from a total of 66 villages. Data analysis in this study used descriptive analysis, variable measurement, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing using SPSS. The results showed that the variables of competence (X1), village government organizational commitment (X2) and budgeting participation (X3) had a positive and significant effect on accountability in village fund management. Keywords: Village Fund, Village Fund Management Accountability, Competence, Village Government Organizational Commitment, Budgeting Participation